Diminuiçao do tempo de setup em linha de embalagem de comprimidos com base na metodologia SMED - Neto, Rubens de Abreu (Universidade Federal de São Carlos, 2025)
The use of machines in industrial processes has been growing, driven by the Industrial Revolution of the 18th century and continuing to grow with the accelerated evolution of manufacturing processes and global technological development. Production processes have undergone several evolutionary changes since the first Industrial Revolution, marked by the introduction of electricity and the implementation of assembly lines in the 19th century. It was during this period that Fordism and Taylorism were consolidated—structures of productive organization that were extremely important in the history of industry. Following this evolutionary path, industrial processes took on a new form in the 20th century, beginning with Toyotism, which adopted the just-in-time system, leading to automated and flexible production lines. This trend was further strengthened by the implementation of robotics, information technology, and electronics in production lines. Toyotism, combined with the technological developments of the 21st century, largely describes the current industrial scenario, where advances are constantly occurring. An example of this is the widespread use of continuous improvement initiatives and agile management methodologies in today's industry. Among the improvement and management tools are Scrum, Lean, Kanban, Nexus, 5S, PDCA, and SMED. SMED is a quick setup tool aimed at fully optimizing the steps and distribution of actions within a setup, resulting in a reduction of its execution time. SMED is extremely important in the current industrial scenario, where the same production line manufactures different products, requiring setup and tooling changes each time the product on the line is switched. Reducing this setup time directly impacts the performance and availability of production lines. This project describes the direct application of the aforementioned methodologies to reduce setup time on a tablet packaging machine in a pharmaceutical industry located in the interior of São Paulo, Brazil. This includes optimizing the sequencing of activities performed by employees when changing the machine’s tools during setups, improving the basic condition of the machine, and optimizing the adjustment process of the critical stages of the process.
Reduction ofsetup time in a tablet packaging line based on the SMED methodology
Keywords: Otimização de produção; Automação; Máquinas; SMED; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO